Augmented reality : an emerging technologies guide to AR - Kipper, Gregory; Rampolla, Joseph (Syngress, 2013)
Augmented reality (AR) is poised to be one of this decade's most disruptive technologies, as the information that is constantly flowing around us is brought into view, in real-time, through augmented reality.